Minimaly Invasive Interventions in Acute Tributary Varicothrombophlebitis of the Lower Extremities - Popovich, Yaroslav M.; Kostiunin, Volodymyr S. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Background. One of the formidable complications of varicose veins of the lower extremities is thrombophlebitis. The risk of developing venous thromboembolic complications remains high even when taking anticoagulants. Most authors do not even consider surgical elimination of the manifestations of acute superficial thrombophlebitis. The aim. To evaluate the effectiveness of minimally invasive surgical treatment of acute tributary varicose veins of the lower extremities. Materials and methods. The surgical treatment of 78 patients with acute varicothrombophlebitis of the tributaries of the great saphenous vein was analyzed. Depending on the treatment performed, patients were divided into two groups: group I including 56 (71.8%) patients who underwent inpatient surgery for thrombotic lesions of varicose veins of the tributaries of the great saphenous vein; group II including 22 (28.2%) patients who received conservative outpatient treatment. Results. The choice of the volume of surgical intervention in patients of group I depended on the condition of thegreat saphenous vein. In the absence of thrombotic and varicose veins in 29 (51.8%) patients, the latter was preserved. With varicose changes in the great saphenous vein, 16 (28.6%) patients underwent radiofrequency ablation after ligationof the thrombosed tributary duct and miniphlebectomy or phlebocentesis with foam-form sclerotherapy. In 11 (19.6%) cases of thrombotic lesions of the great saphenous vein, crossectomy, long/short stripping or phlebocentesis with stem sclerotherapy after ligation of its tributaries and isolation of the latter distal to the thrombotic occlusion was performed. The surgical intervention was supplemented with miniphlebectomy of other varicose veins and ligation of failed perforator veins. In patients of group II, treatment was prescribed similarly to the treatment of deep vein thrombosis. Surgical treatment of patients in group I effectively prevented venous thromboembolic complications and reduced the manifestations of chronic venous insufficiency in 72.9% of cases. Conclusions. Minimally invasive surgical intervention for acute thrombophlebitis of the tributaries of the great saphenous vein allows, on an outpatient basis or in a one-day hospital, to eliminate thrombotic lesions of varicose super-ficial veins and prevent venous thromboembolic complications, reduce or eliminate manifestations of chronic venous insufficiency, prevent recurrence of thrombosis, and reduce the patient’s disability.